Mentoring - Brewerton, Antony (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The literature contains a wide variety of definitions. The Oxford English dictionary – as you might expect – gives a classical definition: mentor. 1. a. With initial capital: The name of the Ithacan noble whose disguise the goddess Athene assumed in order to act as the guide and adviser of the young Telemachus: allusively, one who fulfils the office which the supposed Mentor fulfilled towards Telemachus. b. Hence, as common noun: An experienced and trusted counsellor. [1989]